Graded Children: Evidence of Longrun Consequences of School Grades from a Nationwide Reform - Anna Sjögren (Research Institute of Industrial Economics (IFN), 2010)
Swedish elementary school children stopped receiving written end of year report cards following a grading reform in 1982. Gradual implementation of the reform creates an opportunity to investigate the effects of being graded on adult educational attainments and earnings for children in the cohorts born 19541974, using a difference-in-differences strategy. Accounting for municipal time trends and tracing out reform dynamics, there is some evidence that being graded increases girls years of schooling, but has no significant average effect on boys. Analysis of effects by family background suggests that receiving grades increases the probability of high school graduation for boys and girls with compulsory school educated parents. Sons of university graduates, however, earn less and are less likely to get a university degree if they were graded in elementary school.
Keywords: I21; I28; J13; J24; 330; School policy; Grades; Educational attainment; Adult earnings; Family background; Difference-in-differences; Allgemeinbildende Schule; Schüler; Bewertung; Bildungsabschluss; Wirkungsanalyse; Schweden